Diversity of Native and Exotic Fruit Genetic Resources in Nepal - Gautam, Ishwori Prasad; Gotame, Tek Prasad (Journal of Nepal Agricultural Research Council, 2020)
Diversity in fruit genetic resources in Nepal is contributed by wild, indigenous and exotic sources. This study was carried out to bring together the available fruit species and cultivars at various stations of Department of Agriculture (DoA), Nepal Agricultural Research Council (NARC), Agriculture and Forestry University (AFU) and private farms until the Fiscal Year 2017/2018. Altogether there were 47 species of fruits from tropical zone of Terai (Tarahara, Janakpur, Sarlahi, Parwanipur and Khajura) to cold temperature zone of high hills (Marpha, Rajikot and Satbanj) across the country. Apple diversity was found at Horticulture Research Station, Rajikot, Jumla and has introduced 25 spur type cultivars. National Citrus Research Programme (NCRP), Dhankuta was citrus most diversity areas and has maintained 130 exotic and indigenous germplasms of citrus species followed by NCFD, Kirtipur. Mango diversity was noted at RARS, Tarahara (16 cultivars), RARS, Parwanipur (25 cultivars), Farm of DoA-Sarlahi (30 cultivars), Farms of DoA-Janakpur (18 cultivars), AFU-Rampur (17 cultivars). Some of the private nurseries like Everything Organic Nursery, Patlekhet, Kavre and international organization like Technology Demonstration Centre of ICIMOD, Godawari, Lalitpur were also found to be a diversity centre of many exotic and indigenous germplasms of fruit species. These indigenous fruit genetic resources were also used to develop varieties such as Sunkagati-1 and Sunkagati-2 and Tehrathum Local of acid lime, Khoku Local of mandarin orange, 'Malbhog' of banana which were notified by the National Seed Board, SQCC. The unique fruit genetic resources were ‘Pharping Local’ (Asian sand pear), ‘Sindhuli Junar’ (sweet orange), ‘Dhankuta Local’ and ‘Manakamana Local’ (mandarin), Local Malbhog (banana), Bhaktapure Lapsi (Nepalese hog plum) etc. which have superior traits than exotic fruits. Unique and wild fruit species were yellow, black and red raspberries (Rubus ellipticus, R. foliolosus and R. acuminatus respectively), bale (Aegle marmelos), pummelo (Citrus grandis), citron (Citrus medica), sweet lime (Citrus limettoides), butter tree or chiuri (Basia buttyacea), tamarind (Tamarindus indica), black plum (Syzygium cumini), wild apple (Mallus baccata), rough lemon (Citrus jambhiri), bayberry (Myrica esculanta), edimayal (Pyrus pashia), black and white ebony (Diospyrus malbarica), wild species of olive (Olea ferruginea and O. glandulifera), wild kiwifruit (Actinidia callosa) etc. Most of the diversity studies were based on phenotypic descriptions. We believe that the number of species and genotypes listed in this article would be increased if detail survey is further carried out. Way forward to utilize these valuable genetic resources has also been discussed in this manuscript.